2022
DOI: 10.3389/fpsyg.2022.819049
|View full text |Cite
|
Sign up to set email alerts
|

Cyber victimization and well-being in adolescents: The sequential mediation role of forgiveness and coping with cyberbullying

Abstract: Cyber victimization is an important problem among adolescents and it can have negative effects on well-being. However, efforts to increase the well-being of cyber victims have been increasing in recent years. It is important to uncover the underlying mechanisms that may affect the well-being of cyber victims. This study used the transactional model of stress and coping theory as a conceptual framework, and proposed that hope and coping strategies are sequential mediators for the effects of cyber-victimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 105 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…As shown in Table 1, among the articles included in the present systematic review, ten were conducted in Asia, that is, three in China [52,89,90], two in South Korea [91,92] and the remaining in Indonesia [93], Malaysia [94], Thailand [95], Turkey (eastern Anatolia) [96] and Vietnam [97]; three studies were conducted in European countries, i.e., Croatia [98], Finland [60] and Germany [99]; and the remaining three studies were carried out, respectively, in Australia [100], Canada [101] and Chile [102].…”
Section: Geographical Distribution Period and Methodologies Of Data C...mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, among the articles included in the present systematic review, ten were conducted in Asia, that is, three in China [52,89,90], two in South Korea [91,92] and the remaining in Indonesia [93], Malaysia [94], Thailand [95], Turkey (eastern Anatolia) [96] and Vietnam [97]; three studies were conducted in European countries, i.e., Croatia [98], Finland [60] and Germany [99]; and the remaining three studies were carried out, respectively, in Australia [100], Canada [101] and Chile [102].…”
Section: Geographical Distribution Period and Methodologies Of Data C...mentioning
confidence: 99%
“…Regarding the selected studies' research design, four studies were longitudinal investigations [60,91,92,100], one was a randomized retrospective study [101], and the others were cross-sectional [52,89,90,[93][94][95][96][97][98][99]102].…”
Section: Geographical Distribution Period and Methodologies Of Data C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by (Eroglu et al, 2022) on 12,500 students studying in 46 high schools in Erzurum showed that forgiveness has a positive effect on the health of cyber victims. So, one of the key methods to improve well-being may be to enhance forgiveness.…”
Section: Crime and Forgivenessmentioning
confidence: 99%
“…Bullying and cyberbullying have a negative consequences for physical and mental health (Méndez, Jorquera, Ruiz-Esteban, Martínez-Ramón, & Fernández-Sogorb, 2019). To handle bullying and cyberbullying, forgiveness techniques can be used (Eroglu, Peker, & Cengiz, 2022). The high negative emotional stress reactions and resentment can also be overcome.…”
Section: Effects Of Forgiveness Therapy On Bullying and Cyberbullying...mentioning
confidence: 99%